2018
DOI: 10.1038/s41416-018-0121-y
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index (BMI) trajectories and risk of colorectal cancer in the PLCO cohort

Abstract: Obesity is correlated with increased colorectal cancer (CRC) risk, but few studies have investigated lifetime body mass index (BMI) metrics and CRC risk. In a cohort of 139 229 subjects in the Prostate, Lung, Colorectal, and Ovarian (PLCO) Cancer Screening Trial, we analysed the effects of life-course BMI trajectories on CRC risk. At 13 years of follow-up, 2031 subjects developed CRC. Compared with subjects who were never overweight/obese, subjects who first exceeded the threshold of 25 kg m at age 20 had a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 15 publications
6
25
0
1
Order By: Relevance
“…On the other hand, cancers of the digestive system (colon, pancreas and liver), for which oestrogens can have protective effects, did not show prominent positive associations with weight gain in middle adulthood, despite clear positive associations with maintaining OW or OB BMI category. In agreement with our findings, published epidemiological studies have provided little evidence for positive associations of short‐term weight gain with colorectal cancer, 8,10,22,35 but an inverse association has been reported with intentional weight loss, 25 which we have observed for weight loss from OW to NW BMI category. Although mechanistic studies have shown that colonocyte proliferation increases with weight gain and decreases with weight loss, 36 it has also been suggested that weight gain in middle adulthood is less hazardous for colorectal cancer compared to weight gain during early adulthood 8,37 .…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, cancers of the digestive system (colon, pancreas and liver), for which oestrogens can have protective effects, did not show prominent positive associations with weight gain in middle adulthood, despite clear positive associations with maintaining OW or OB BMI category. In agreement with our findings, published epidemiological studies have provided little evidence for positive associations of short‐term weight gain with colorectal cancer, 8,10,22,35 but an inverse association has been reported with intentional weight loss, 25 which we have observed for weight loss from OW to NW BMI category. Although mechanistic studies have shown that colonocyte proliferation increases with weight gain and decreases with weight loss, 36 it has also been suggested that weight gain in middle adulthood is less hazardous for colorectal cancer compared to weight gain during early adulthood 8,37 .…”
Section: Discussionsupporting
confidence: 92%
“…The results of the present study and those of other studies, including the study by Zheng et al (20), showed that the body mass index of people with CRC before their illness was significantly higher than those who did not have cancer. This suggests that patients may have consumed too much high-fat and high-sugar foods and have not had much exercise or activity.…”
Section: Discussionsupporting
confidence: 73%
“…It is proven that obese individuals have higher risk of colorectal adenoma, advanced adenoma, and CRC. 2,15,16 However, it is not fully understood whether this is due to acceleration of adenoma formation only (i.e. acceleration of normal to adenoma sequence) or acceleration of the whole carcinogenesis and progression process.…”
Section: Discussionmentioning
confidence: 99%